Seismic responses of sea-crossing isolated continuous beam bridges considering seabed–pile–seawater–bridge interaction. (July 2022) - Fu, Jianyu; Tong, Lei; An, Zhenghan; Wang, Dongsheng
Highlights: The sea-crossing isolated continuous beam model considering the seabed–pile–seawater–bridge interaction is established using the ADINA software. The influence of the coupling system on the seismic response of the sea-crossing isolated continuous beam bridge is investigated. The position of the pile cap effect on the seismic isolation for the continuous beam bridge is compared. Abstract: To consider the multiple interactions between offshore sites and sea-crossing bridges under seismic actions, a seabed–pile–seawater–bridge interaction model is established by the ADINA software [1] . This study uses seismic fluctuation analysis as an input to bedrock ground motion. It reflects the influence of submarine sites and seawater layers on ground motion characteristics through the fluid-solid coupling of seawater to the seabed. It was found that the whole bridge piers considering the coupling effect are in an elastic state. The yielding of the isolated bearings occurs. Also, the seismic response of the bridge structure under the seabed-pile-seawater-bridge interaction is significantly higher than those under the direct input of the ground motions from the fixed basement assumption. In addition, when the pile cap is above the seabed, the average seismic response of the bridge structure is 1.2–1.3 times the response when the pile cap is below the seabed. Therefore, the seismic design of marine structures should take full account of the influence of the submarine site and the seawater layer. Otherwise, it will result in greater seismic risks for marine structures such as sea-crossing bridges. In addition, this study also suggests the influence of the pile cap location on the seismic response of the bridge.